Influences of Exit Advance Guide Signs on the Trajectory and Speed of Passenger Cars in Highway Tunnels - Ting Shang; Peng Wu; Guan Lian; Qijin Sheng (Journal of Advanced Transportation)
The driving behavior in highway tunnels is more complicated than that in regular roadbed sections because the former is usually affected by black and white hole effects, tunnel clearance, and bad illumination. Unfortunately, the current Chinese criteria and the Uniform Traffic Control Equipment Manual (MUTCD) 2009 guidelines provide no clear method for setting exit advance guide signs in highway tunnels. Hence, a driving simulator-based experiment was conducted in the current study to analyze the effects of exit advance guide signs on the trajectory, speed, and acceleration of passenger cars in a highway tunnel under three different service levels. It was found that when the service level is first service level, second service level, and third service level, the setting of the exit advance guide signs made the initial transverse location of the vehicle from the tunnel exit advance by 13.39%, 21.20%, and 5.73%, the lane change distance is shortened by 6.34%, 20.18%, and 15.34%, the average speed is decreased by 1.44%, 2.40%, and 0.08%, and the acceleration is decreased to −0.10 m·s−2, −0.11 m·s−2, and −0.06 m·s−2. Thus, the exit guide signs in the tunnel played a certain optimization role in improving the traffic flow state of the section and reducing the traffic accident rate.